Pengaruh Direct Marketing, Store Atmosphere, dan Locatioan terhadap Kepuasan Pelanggan - Monica Banjarsari; Setio Utomo (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2026)
The purpose of this study is to examine and analyze the influence of direct marketing on customer satisfaction at Cinnamon Coffee and Eatery Banjarbaru, to analyze the influence of store atmosphere on customer satisfaction, to analyze the influence of location on customer satisfaction, and to analyze the simultaneous influence of direct marketing, store atmosphere, and location on customer satisfaction at Cinnamon Coffee and Eatery Banjarbaru. This study employs a quantitative research method using multiple linear regression analysis. Data were collected through the distribution of questionnaires. The population in this study consists of customers who visited Cinnamon Coffee and Eatery Banjarbaru, with a sample of 100 respondents selected using purposive sampling technique. The results show that direct marketing and store atmosphere have a positive and significant influence on customer satisfaction at Cinnamon Coffee and Eatery Banjarbaru. On the other hand, location has a negative and insignificant influence on customer satisfaction. However, simultaneously or partially, all three variables direct marketing, store atmosphere, and location are proven to have a significant effect on customer satisfaction